4th order current-mode and transresistance-mode MOSFET-C low-pass filter for multi-standard receivers. (September 2021) - Yesil, Abdullah; Ozenli, Deniz
Abstract: This work presents a novel 4th order current-mode and transresistance-mode low-pass filter based on MOSFET-C architecture. Proposed filter's cut-off frequency can be easily adjusted from 15 MHz up to 45 MHz for the analog baseband filters used in multi-standard receivers. The main core circuit of the filter contains only 7 transistors in order to reduce chip area and power consumption. Also, the proposed 4th order architecture have dual outputs in different modes facilitating signal conversion and different signal operations. The proposed structure has (54.3 μm × 34.1 μm) chip area and post layout simulations are examined extensively to prove performance of the filter. Also, input referred noise (IRN) characteristics of the filter outputs are shown in order to overcome thermal noise effects worsening the performance of the filter. Power consumption changes from 195.8 μW up to 1.37 mW whereas cut-off frequency is varied from 15 MHz up to 45 MHz. Provided results show that the proposed filter scheme brings a promising opportunity to designers for the analog baseband operations in multi-standard communication receivers.